An optical test strip for the detection of benzoic acid in food - Hamzah, Hairul Hisham; Yusof, Nor Azah; Salleh, Abu Bakar; Abu Bakar, Fatimah (MDPI, 2011)
Fabrication of a test strip for detection of benzoic acid was successfully implemented by immobilizing tyrosinase, phenol and 3-methyl-2-benzothiazolinone hydrazone (MBTH) onto filter paper using polystyrene as polymeric support. The sensing scheme was based on the decreasing intensity of the maroon colour of the test strip when introduced into benzoic acid solution. The test strip was characterized using optical fiber reflectance and has maximum reflectance at 375 nm. It has shown a highly reproducible measurement of benzoic acid with a calculated RSD of 0.47% (n = 10). The detection was optimized at pH 7. A linear response of the biosensor was obtained in 100 to 700 ppm of benzoic acid with a detection limit (LOD) of 73.6 ppm. At 1:1 ratio of benzoic acid to interfering substances, the main interfering substance is boric acid. The kinetic analyses show that, the inhibition of benzoic is competitive inhibitor and the inhibition constant (Ki) is 52.9 ppm. The activity of immobilized tyrosinase, phenol, and MBTH in the test strip was fairly sustained during 20 days when stored at 3 °C. The developed test strip was used for detection of benzoic acid in food samples and was observed to have comparable results to the HPLC method, hence the developed test strip can be used as an alternative to HPLC in detecting benzoic acid in food products.